Etika profesi guru sebagai landasan pembentukan budaya sekolah di MTSN 4 Pasuruan - Zaky, Moch Asyrof (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the role of teachers’ professional ethics in shaping school culture at MTsN 4 Pasuruan. Teachers’ professional ethics are viewed as a moral foundation that influences behavior, interactions, and the quality of learning within the school environment. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and documentation. The findings reveal that teachers at MTsN 4 Pasuruan consistently apply ethical values such as honesty, responsibility, and discipline in both teaching practices and social interactions. Teachers’ exemplary conduct serves as a key factor in fostering a school culture that is religious, disciplined, and collaborative. In addition, the support of the school principal and internal policies further strengthen the implementation of professional ethics within the institution. Despite challenges such as differing perceptions and administrative burdens, ethical practices remain consistently upheld through communication and collective reflection. This study concludes that teachers’ professional ethics are a vital foundation for building a positive and sustainable school culture